The Influence of Leadership Style and Motivation on Employee Performance at SMP Negeri 46 Jakarta - Bambang Harmoko; Swasta Bangun (CV Putra Publisher, 2024)
The purpose of this research is to determine the influence of Leadership Style and Motivation on Employee Performance at SMP Negeri 46 Jakarta using a research sample of 38 employees with data analysis techniques using multiple regression analysis. The research results show an R Square value of 0.633, meaning that Leadership Style (X1) has a significant effect on Employee Performance (Y) by 63.3%, while the remaining 36.7% is caused by the influence of other factors that were not studied. The R Square value of 0.701 means that Motivation (X2) has a significant effect on Employee Performance (Y) by 70.1%, while the remaining 29.9% is caused by the influence of other factors that were not studied. The Adjusted R Square value of 0.813 means that Leadership Style (X1) and Motivation (X2) have a joint and significant effect on Employee Performance (Y) of 81.3%, while the remaining 18.7% is caused by the influence of other variables that are not examined in this research.